Identification of FKBP10 prognostic value in lung adenocarcinoma patients with surgical resection of brain metastases: A retrospective single-institution cohort study - Liu, Zhi-Dan; Wang, Song-Quan; Li, Sai; He, Jie; Wang, Shao-Hua; Cai, Hong-Qing; Wan, Jing-Hai (Clinics, 2023)
Objective: To explore the expression levels and clinical value of FKBP10 in lung adenocarcinoma brain metastases. Design: A retrospective single-institution cohort study. Patients: The perioperative records of 71 patients with lung adenocarcinoma brain metastases who underwent surgical resection at the authors’ institution between November 2012 and June 2019 were retrospectively analyzed. Methods: The authors evaluated FKBP10 expression levels using immunohistochemistry in tissue arrays of these patients. Kaplan-Meier survival curves were constructed, and a Cox proportional hazards regression model was used to identify independent prognostic biomarkers. A public database was used to detect FKBP10 expression and its clinical value in primary lung adenocarcinoma. Results: The authors found that the FKBP10 protein was selectively expressed in lung adenocarcinoma brain metastases. Survival analysis showed that FKBP10 expression (p = 0.02, HR = 2.472, 95% CI [1.156, 5.289]), target therapy (p < 0.01, HR = 0.186, 95% CI [0.073, 0.477]), and radiotherapy (p = 0.006, HR = 0.330, 95% CI [0.149, 0.731]) were independent prognostic factors for survival in lung adenocarcinoma patients with brain metastases. The authors also detected FKBP10 expression in primary lung adenocarcinoma using a public database, found that FKBP10 is also selectively expressed in primary lung adenocarcinoma, and affects the overall survival and disease-free survival of patients. Limitations: The number of enrolled patients was relatively small and patients’ treatment options varied. Conclusions: A combination of surgical resection, adjuvant radiotherapy, and precise target therapy may benefit the survival of selected patients with lung adenocarcinoma brain metastases. FKBP10 is a novel biomarker for lung adenocarcinoma brain metastases, which is closely associated with survival time and may serve as a potential therapeutic target.